Investigating stem cell interactions using Atomic force microscopy - Graumuller, Friedrich (2019)
Embryonic stem cells (ESC’s) hold great promise for future clinical therapies including for tissue replacement due to their remarkable capabilities for self-renewal and pluripotency. While most studies in the field of stem cell research have focused on how biochemical factors, signaling pathways, and transcriptional networks control differential gene expression, few studies have investigated the impact of mechanical signals such as cell adhesion on stem cell behavior. E-cadherin is a unique target to study the importance of mechanical signals in embryonic stem cell differentiation. Not only is it associated with maintaining the pluripotency of ESC’s but it also functions as an adhesive molecule. Atomic force microscopy (AFM) has been shown to be an effective tool to examine the molecular interaction forces between cadherin molecules immobilized on solid surfaces and cells. This thesis thus aimed to explore for the first time E-cadherin interactions on the surface of undifferentiated ESC’s using AFM. First a surface functionalization technique was developed to demonstrate that it was possible to attach recombinant E- cadherin ectodomain constructs to AFM tips and silicon surfaces and to measure their interactions by AFM force measurements. By bringing functionalized AFM tips and surfaces into and out of contact the force necessary to rupture formed E-cadherin bonds, as well as the frequency of bond formations could be quantitatively measured. For comparison the binding behavior of the classical cadherin N-cadherin was also assessed using the same type of experiments. Rupture forces for homophillic and heterophillic bonds between the E and N cadherin ectodomains had modal rupture forces that were in agreement with forces reported in literature using similar methodology (20-80pN). E- and N-cadherin bond rupture forces were found to decline with increasing AFM tip speeds. After having studied cadherin interactions at the single molecule level, the same methodology was used to study cadherin bond formations on mouse embryonic stem cells (mESC’s). It was possible to measure bond strengths and frequencies of interactions between the cadherin ectodomain constructs immobilized on AFM tips and native cadherin on the cell surface. E- and N-cadherin bond rupture forces strongly resembled those previously measured in single molecule experiments (i.e.<10 pN difference). In preliminary experiments it was possible also to detect potential differences in E-cadherin interactions when mES cells were allowed to differentiate into precursor cells of the neuronal lineage, suggesting that that a lineage specification of undifferentiated mES cells goes hand in hand with a change of E-cadherin mediated adhesion. Lastly, a model system based on holographic optical tweezers (HOT) was developed as an alternative approach to AFM to investigate cadherin interactions on mES cells. Optical tweezers possess a unique potential to explore the nature of cadherin interactions, with a greater resolution of detecting bond rupture forces compared to AFM. Although it was possible to investigate interaction forces between trapped silicon beads, E-cadherin coated beads and mES cells, several technical issues were identified in our experiments; for example the close proximity of optical traps was found to cause interference and resulted in irregularities of force curves. With further development this approach could be used as a tool to advance stem cell research, by identifying the pluripotent state as well as other stages of development based on physical, rather than by using chemical or genetic cues. This could be of great benefit in cancer research when discriminating between normal and cancerous cells, as well as in regenerative medicine, tissue engineering, drug discovery, disease modelling and developmental biology.